SATELLITE HIGHT SPEED ROTOR-EQUIPMENT LAYOUT OPTIMIZATION ＆ STIMULATION FOR REDUCING STATIC UNBALANCE DISTURBANCE - ZHAO Hua; FAN Ning; YU Kuai (Jixie qiangdu)
Momentum wheel、CMG etc high speed rator-equipmentsareimportantnoiseoriginswhich haveabadinfluence on in-orbit satellite stability. As space resolution raisingandexposuretimeincreasing,disturbance influence become greater to image qulity,so reducing disturbance of high speed rotor is one of key design items for high-resolution optical remote sensing satellite on GEO robit. Currently multiple effective schemes have been presented to solve the problem by researchers,astrategy is discussed and proposed to reducing disturbance resulting from static unbalance base on rotor-equipment layout. With optimization and stimulation,theresults show that the method is valid to reducing disturbance from static unbalance by using layout optimization.